(untitled) (Texas Journal of Medical Science, 2023)
Inflammatory and degenerative spinal diseases are one of the pressing problems of modern rheumatology due to the high prevalence, frequent incidence of diseases of young and middle-aged men, frequent lesions of internal organs, early disability of patients, socio-economic damage caused to the patient and society [1]. Since 1892, when V.M.Bekhterev described the main clinical manifestations of the disease and suggested that it should be singled out as a separate nosological form, researchers from the leading countries of the world have achieved certain success in studying its nature, mechanisms of development, as well as treatment and rehabilitation of patients. Nevertheless, ankylosing spondylitis (AC), which is regarded as a disease of the musculoskeletal apparatus, affecting mainly young men, remains one of the leading socioeconomic problems of our time, leading to disability in working age.